2014
DOI: 10.1038/srep04102
|View full text |Cite
|
Sign up to set email alerts
|

Tumor derived vasculogenesis in von Hippel-Lindau disease-associated tumors

Abstract: von Hippel-Lindau disease (VHL) patients develop highly vascular tumors, including central nervous system hemangioblastomas. It has been hypothesized that the vascular nature of these tumors is the product of reactive angiogenesis. However, recent data indicate that VHL-associated hemangioblastoma neoplastic cells originate from embryologically-arrested hemangioblasts capable of blood and endothelial cell differentiation. To determine the origin of tumor vasculature in VHL-associated hemangioblastomas, we anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…2 Several studies have indicated that VHL deficient hemangioblastoma precursor cells, tumorlets, are established during embryonic development, although the exact tumorigenesis is still unknown. [17][18][19][20][21][22] Thus, from birth, vHL patients may harbor numerous microscopic tumorlets in the CNS, including the retina, and similar growth patterns would be expected. Differing anatomical and diagnostic limitations may account for some of the observed disparity in tumor development at the two sites.…”
Section: Variation In Manifestation Rate Depends On the Anatomical Lomentioning
confidence: 99%
“…2 Several studies have indicated that VHL deficient hemangioblastoma precursor cells, tumorlets, are established during embryonic development, although the exact tumorigenesis is still unknown. [17][18][19][20][21][22] Thus, from birth, vHL patients may harbor numerous microscopic tumorlets in the CNS, including the retina, and similar growth patterns would be expected. Differing anatomical and diagnostic limitations may account for some of the observed disparity in tumor development at the two sites.…”
Section: Variation In Manifestation Rate Depends On the Anatomical Lomentioning
confidence: 99%
“…In cases of VHL disease where the VHL gene is mutated, VHL protein does not bind to HIF1α and activates the expression of a number of factors, including vascular endothelial growth factor, platelet-derived growth factor, erythropoietin, and transforming growth factor, which lead to angiogenesis and tumorigenesis. [5,6] …”
Section: Discussionmentioning
confidence: 99%
“…demands and minimal to no energy reserves, which exacerbate genetic defects in mechanisms regulating metabolism and oxygen sensing (114). While VHL-mediated kidney cancer involves vascular remodeling via angiogenesis, hemangioblastoma formation in neurological tissues of VHL patients may also involve vasculogenic processes (113,115,116). The precise cellular contribution of vascular cells versus tumor "stromal" cells to the dense vascularity of hemangioblastomas remains an open question (113); it is clear, however, that excessive proangiogenic factors such as VEGF-A, PDGF-BB, and EGF drive lesion growth (117,118).…”
Section: Angiogenesis In Vhl Disease -Beyond the Kidneymentioning
confidence: 99%